Teacher-Learner-Resources Instructional Interaction Pattern and Secondary School Learners' Attainment in Biology in Kakamega County-Kenya - Vakhoya, Nasiali Ebby; Masibo, Edwin Masibo; Nabwire, Christine Nabwire (Journal of Education and Practice, 2022)
Purpose: The performance of learners' in Science subjects has been below average over the years in many countries; hence causing concern among the education stakeholders. Poor performance in Biology and the intervention mechanisms on methodology within Kakamega Central Sub County has not been documented. This study endeavored to fill this gap by assessing how an improvement on instructional interaction patterns can positively influence the learners' attainment in Biology. The aim of this study was to assess the effect of teacher-learner-resources instructional interaction pattern on secondary school learners' attainment in Biology. Methodology: The study adopted the constructivism theory as advanced by Jerome Bruner, alongside a conceptual framework based on the objective of the study. A Quasi-experimental Solomon four-group design was used. The target population was one Quality Assurance and Standards Officer, thirty-two secondary school Principals, one hundred and twenty-eight teachers of Biology and, one thousand, four hundred and forty form three students of Biology from thirty-two secondary schools in Kakamega Central Sub County. Stratified sampling, simple random sampling and purposive sampling procedures were employed in the study. Data was collected through use of Learners' Achievement Tests, questionnaires, interview schedule and direct classroom observation. Data collected was analyzed using descriptive and inferential statistics. Results: The findings showed a significant improvement in the post-test scores as compared to the pre-test scores. This indicated that the teacher-learner-resources instructional interaction pattern influenced better attainment of Biology among secondary school learners. Unique Contribution to Theory, Policy and Practices: The study therefore recommends teachers of Biology to be encouraged to use relevant learning resources while teaching. The teachers of Biology are to be encouraged to use relevant teaching-learning resources while teaching. Similarly, learners to be allowed to learn through a multi-sensory approach because it caters for the different learning styles that enhances their attainment in Biology.